Variation of Radio Refractivity with Height above Ground - Valma, E.; Tamosiunaite, M.; Tamosiunas, S.; Tamosiuniene, M.; Zilinskas, M. (Elektronika ir Elektrotechnika, 2011)
In Vilnius, the daily and the seasonal variations of the radio refractivity values have been computed at the Earth surface in the years 2005-2010 and at the heights up to 1.2 km in November 2010. The International Telecommunications Union - Radiocommunications Sector (ITU-R) model was used for calculation of the radio refractive index according to the peculiarities of climatic conditions of Lithuania. As a result of obtained data analysis, the days with more variable meteorological parameters have been chosen for more detailed investigation. The radio refractivity gradient has been computed at the heights starting from the Earth surface up to 1.2 km above the ground, using the meteorological data measured at those heights. The variation of radio refractivity and its gradient are influenced by the changes in air’s humidity and temperature in most part. Ill. 7, bibl. 17, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.349